Students' Algebraic Errors Regarding Linear Equations and Inequalities in One Variable - Ummul Khaira; Naufal Asyqar Fatio (CV. Edujavare Publishing, 2026)
This study aims to identify students' algebraic errors regarding linear equations and inequalities in one variable. A qualitative research method employing a hermeneutic-phenomenological approach was used; data were collected by administering an algebra test on the topic to identify errors and conducting student interviews to determine the underlying causes. The research subjects were students at an Islamic junior high school (MTs) who had already studied linear equations and inequalities in one variable. The results revealed that 52.85% of students answered incorrectly on the test, with the highest error rate (70%) observed in question number 5 and the lowest (26.67%) in question number 4. Four categories of algebraic errors were identified, spanning seven out of ten specific error subcategories. Four of these subcategories related to students' understanding of arithmetic operations and mathematical interpretation (mathematization), while the remaining three related to their understanding of the topic's definitions.